Catalytic hydroesterification of lignin: a versatile and efficient entry into fully biobased tunable materials. Issue 5 (8th February 2023) - Buhaibeh, Ruqaya; Richard, Tiphaine; Gauvin, Régis M.; Sauthier, Mathieu; Dumont, Clément
Abstract : Hydroxyl groups of several industrial grade lignins are esterified by palladium-catalyzed hydroesterification reactions with CO and olefins, fatty esters or 1, 3-butadiene. Abstract : Hydroxyl groups of several industrial grade lignins are esterified by palladium-catalyzed hydroesterification reactions with CO and olefins, fatty esters or 1, 3-butadiene. The reaction is efficient and salt-free and allows the introduction of aliphatic chains to lignin through the ester linkage. Technical and modified lignins are characterized by NMR, IR, and SEC and their thermal properties are evaluated by DSC. The esterified lignins show modified glass transition temperatures that depend on the substitution degree of the hydroxyl groups and on the nature of the aliphatic chains that have been introduced. The implementation of this catalysis also provides the possibility of inserting new reactive functionalities such as esters or unsaturations from abundant and/or biobased reactants.